The entrepreneur motivation and financing sources - Anthony Abiodun Eniola (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The paper is to examine the influence of business innovation, business expansion, product and service development, working capital, and machinery and equipment requirement on financing choices in the western part of Nigeria. To determine the effect on financing choices, a logistic regression analysis was used. The results, in an impressive manner, indicate that entrepreneurs, essentially with working capital (WC), machinery and equipment (ME) requirements, and business innovation (BI), use internal funding sources, while business expansion (BE) and product and service (PS) development lean toward external funding sources, and more established and larger firms utilize debt financing. The approach and experiential findings offer an unprecedented degree of investigation of previous studies of Nigerian entrepreneurs. Similarly, the experimental results will strengthen entrepreneurs' knowledge, awareness, and perception. Through their own capabilities, entrepreneurs can prepare and adapt in accordance with the business conditions in which they conduct business, and this work may help them in their choice procedure regarding the capital structure of their organization in the midst of a period when the question of entrepreneur funding is gradually emerging in the Nigerian climate.
Keywords: 650; business innovation; entrepreneur; financing choices; machinery and equipment; motivation; Nigeria; resource-based view; working capital